ALGAE FLORA OF THE FIELDS PLANTED IN ALFALFA (Academicia Globe: Inderscience Research, 2023)
It has been hypothesized that algae in bedassore fields soils overlooking agricultural arable fields in the southern sarkhads of the Fergana Valley occur at different depths, different temperatures and conditions with different moisture levels, according to which the number of species in the Cyanophyta section was the highest, followed by the Chlorophyta section algae and The Last by the Xanthophyta section algae.